(untitled) (Biological Sciences - PJSIR, 1995)
Inagreenhouseexperiment,chickpea(CM-72)wassubjectedtodifferentsalinitylevelsunderun-inoculated and rhizobialinoculationtostudyeffectiveness (noduleformation)andgrowthoftheplant.Tnasetofinoculatedplants,the plantsdiedat6.0 dSrrr’ andbeyondatfloweringstageshowingtheirsensitivitytowardsalinity.Plantheight,drymatter yield(DMY),N-content(mg/plant)decreasedwithincreasingsalinitylevelsinbothinoculatedandun-inoculated plants atallgrowth stages.Nodulationwasadverselyaffectedduetopresenceofsalinityinthegrowthmedium.Percentcrude proteinincreased withincreasingsalinity.Percentcrudeproteincomparativelyincreasedininoculated plantsthan un- inoculatedones.Chickpeaissensitivetosalinity.Seedtreatmentwithrhizobialinoculummayimprovetheproteincon-’ tent of plant under saline conditions.